A Study on the Educational and Professional Trajectory of the Graduates from a Private University Institution in the City of Buenos Aires - Elizondo, Cristina M.; Eymann, Alfredo; Carrió, Silvia; Ladenheim, Roberta; Olivar, Griselda; Eder, María Laura (Revista del Hospital Italiano de Buenos Aires, 2023)
The evaluation of learning and how it translates into the professional life of students is a source of concern for educational institutions responsible for training professionals for social purposes. We aimed to explore the relationship between the studies completed by our graduates and their professional trajectories based on their prospects. For our cross-sectional study, we included all undergraduates, graduates, and postgraduates from 2001 onwards. We sent out the questionnaire by mail. Out of 1,691 graduates, we sent the questionnaire to 1,446; 410 (28.4%) returned it. 95.5% are currently employed, and 92.7% perceived that the training received is related to the present job. Ninety-one percent agreed and strongly agreed that the theoretical training was adequate for their current professional job. Seventy-nine percent considered that the practical training was also relevant. Fifty-one percent are currently performing teaching activities, 36% are working in research activities, and 36% are performing dissemination or knowledge transfer activities. 83% remain in academic, work, or social relationships with former classmates. Their average score for training was 8.7, and 98.3% of graduates would recommend studying at our University to their friends. Most of them felt that the theory and practical training they received were adequate for their current professional work. Most of them have a job closely connected to their studies at the University.